2016
DOI: 10.1161/circulationaha.115.019124
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Wearable Cardioverter-Defibrillator in Patients at High Risk for Sudden Cardiac Death

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 20 publications
11
89
4
3
Order By: Relevance
“…These findings contrast with a previously published study that did not show any WCD shock in 254 patients with newly diagnosed NICM . However, the incidence of zero ventricular tachyarrhythmias in this cohort is not supported by the majority of WCD studies in NICM patients and might be partly explained by a shorter WCD wearing time of 71 days (median) . Another recent study on patients with NICM wearing the WCD already reported a relevant risk for ventricular tachyarrhythmias in newly diagnosed HF .…”
Section: Discussioncontrasting
confidence: 99%
“…These findings contrast with a previously published study that did not show any WCD shock in 254 patients with newly diagnosed NICM . However, the incidence of zero ventricular tachyarrhythmias in this cohort is not supported by the majority of WCD studies in NICM patients and might be partly explained by a shorter WCD wearing time of 71 days (median) . Another recent study on patients with NICM wearing the WCD already reported a relevant risk for ventricular tachyarrhythmias in newly diagnosed HF .…”
Section: Discussioncontrasting
confidence: 99%
“…There are some important distinctions when comparing compliance data in this open‐label randomized trial compared with previously published registry studies 9–12 . In our study, the denominator of the percentage wear‐time is all participants who were randomized to that group, whereas in the registry, these were patients who were prescribed and wore the WCD as part of clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…WCD use has been proven safe and effective [16][17][18][19]. Data published in 2015 from the WEARIT-II Registry showed that devices could be safely used.…”
Section: Introductionmentioning
confidence: 99%